2011
DOI: 10.5897/ajb11.186
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering and thermodynamic characterization of an extracellular -glucosidase produced by Aspergillus niger

Abstract: The production of an extracellular β-glucosidase by Aspergillus niger NRRL 599 was optimized using submerged fermentation technique. Effect of different media, different carbon sources, initial pH of the fermentation medium, temperature, incubation period and inoculum size on the production of β-glucosidase enzyme was investigated. A. niger NRRL 599 produced maximum extracellular β-glucosidase (4.48 U/mg) in Eggins and Pugh medium with 1% wheat bran (w/v) at pH 5.5 inoculated with 4% conidial suspension after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…The optimum incubation temperature obtained in this study is quite similar to that reported by Bansal et al (2012) and Zahoor et al (2011). In their experiments, A. niger NS-2 was used to produce β-glucosidase using wheat bran as substrate (Bansal et al 2012), while Zahoor et al (2011) produced β-glucosidase from A. niger NRRL 599, resulting in optimum temperature for enzyme production at 30 o C.…”
Section: Effect Of Incubation Temperature On Enzyme Productionsupporting
confidence: 84%
See 3 more Smart Citations
“…The optimum incubation temperature obtained in this study is quite similar to that reported by Bansal et al (2012) and Zahoor et al (2011). In their experiments, A. niger NS-2 was used to produce β-glucosidase using wheat bran as substrate (Bansal et al 2012), while Zahoor et al (2011) produced β-glucosidase from A. niger NRRL 599, resulting in optimum temperature for enzyme production at 30 o C.…”
Section: Effect Of Incubation Temperature On Enzyme Productionsupporting
confidence: 84%
“…Most filamentous fungi will grow optimally and secrete high production of enzymes in acidic pH (Zahoor et al 2011). This might be due to the fact that alkaline pH has inhibitory effect on fungal growth and enzyme production.…”
Section: Effect Of Initial Fermentation Ph On Enzyme Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…Submerged fermentation technique had been reported for its use in the extracellular production of BGS by different Aspergillus strains (Gunata and Vallier 1999; Jager et al 2001). Zahoor et al (2011) reported the use of submerged fermentation technique for the maximum yield of BGS by Aspergillus niger in the Eggins and Pugh containing wheat bran (1%). A recent study by Mallek-Fakhfakh et al (2017) have reported the BGS producing Talaromyces thermophilus with the agricultural waste as a substrate using submerged fermentation technique.…”
Section: Introductionmentioning
confidence: 99%